PEMETAAN DAERAH RAWAN KONFLIK ORANGUTAN SUMATERA (Pongo abelii) DENGAN MANUSIA DI DESA SEKITAR CAGAR ALAM DOLOK SIBUAL-BUALI - Diyanti Isnani Siregar; Anita Zaitunah; Pindi Patana (Peronema Forestry Science Journal, 2015)
is Sumatran Orangutan (Pongo abelii). as a result of orangutan habitat fragmentation, there are problems arised such as conflicts between human and orangutan. This study aims to do mapping conflict area and analyze the biophysical factors that support the conflict between orangutan and the villagers around Dolok Sibual-buali Natural Reserve. By using the coordinates of human-orangutan conflict location, and then processed using Geographic Information System application to identify several factors such as altitude, slope, distance from the river, distance from the road, distance from the forest area, and the land use.  This research showed that the human orangutan conflict-prone area is in the location with secondary tropical dry land forest cover type in the altitude between 742-1051 m asl, at 0-8%, 8-15%, 15-25% range of slope and the distance around 0-4250 meters from Dolok Sibual-buali Natural Reserve area. The result of Rank Spearman correlation test showed that the strongest physical factor effect of this case is the field’s distance from forest area and the weakest effect is the field’s distance from the river.Keywords: Orangutan Sumatra, Human-orangutan conflict,Conflict Area Mapping, Dolok Sibual-buali Natural Reserve